CREST Demand Model - Eoghan McKenna; Murray Thomson; John Barton (2015)
The model is an integrated thermal-electrical demand model based on a bottom-up activity-based structure, using stochastic programming techniques to represent dwelling diversity, producing calibrated and validated output at high-resolution, based on reduced-order thermal-electrical networks to represent thermal dynamics, and developed as free open-source software to promote transparency and further research.Please note that there are some minor bugs in previous versions of the software (versions 2.3 and 2.3.1) that would cause small numerical errors and in some cases could stop the the programme working depending on the version of Excel used.Version 2.1 of this model was uploaded on 1st December 2015.Version 2.2 of this model was uploaded on 19th April 2016.Version 2.3 of this model, now capable of modelling Indian households was uploaded on 5th February 2018Version 2.3.1 was uploaded on 2nd November 2018.Version 2.3.3 was uploaded on 15th May 2020.